Chapter 4: Determinants of aggregate import demand in Bangladesh - Tang, T.C. (Bangladesh Development Initiative (BDI) - The University Press Limited (UPL), 2008)
The Bangladesh Economy: Diagnoses and Prescriptions represents a compilation of articles drawn from the Journal of Bangladesh Studies where they were originally published at various times. The selection of the articles was predicated on two main criteria: their immediate relevance to the Bangladesh economy and the reputation of the authors who have a solid record of publications in international journals where they have influenced the thinking of others through their insightful writing.